Climate Change, Cattle-Rearing and Creation of Ranches to Protect the Environment in Southwest, Nigeria - Olusola, Owagbemi Gabriel (Review of Environment and Earth Sciences, 2018)
This paper investigates the environmental destructions caused by cattle-grazing in Southwest, Nigeria, challenges associated with herding activities and measures to protect the environment from further destruction. For a qualitative analysis, 10 focus group discussions consisting of 6–10 participants and 4 in-depth interviews were conducted with selected farmers, Fulani herdsmen, and traditional rulers. Data collected were analyzed using content analysis. Respondents reported environmental destruction caused by the cattle-grazing activities of the Fulani herdsmen in the Southwest Nigeria, these range from destruction of crops due to the invasion of farmlands by cattle, destruction of green vegetation, destruction of young seedlings and water pollution. They also identified the challenges associated with the cattle-grazing activities of the herdsmen as lack of trust among the ethnic groups/ethnic stereotyping; suspicion; overgrazing on fallow lands; kidnapping/killing. Finally, the participants made the following suggestions on measures to protect the environment: the creation of cattle ranches; provision of hays/foray for cows’ consumption; enlightenment on the danger of open grazing and the advantage of cattle ranches. The paper concludes by highlighting some policy options, the Federal Government of Nigeria (FGN) should sensitize Nigerians on the need for creation of cattle ranches in some parts of the country; the Fulani herders should be educated on how to rear cows without infringing on the right of others; FGN should encourage the provision of hays/foray for cows’ consumption and the herdsmen should be compelled to buy this for their cows; and government at all level should enact anti open-grazing law.